Mechanisms by which end-of-life communication influences palliative-oriented care in nursing homes: A scoping review. Issue 12 (December 2019) - Gonella, Silvia; Campagna, Sara; Basso, Ines; De Marinis, Maria Grazia; Di Giulio, Paola
Highlights: End-of-life communication enhances family understanding, shared decision-making, and knowledge of resident's preferences. Understanding promotes shared decision-making between family and healthcare professionals. Delayed conversations negatively impact on transition from curative to palliative care. Abstract: Objective: End-of-life communication has been largely recognized to promote quality end-of-life care in nursing home (NHs) by increasing residents' likelihood of receiving comfort-oriented care. This scoping review summarizes what is known about the potential mechanisms by which end-of-life communication may contribute to palliative-oriented care in NHs. Methods: Using the framework proposed by Arksey and O'Malley and refined by the Joanna Briggs Institute methodology, five literature databases were searched. We extracted 2159 articles, 11 of which met the inclusion criteria: seven quantitative, three qualitative, and one mixed-methods study. Results: Three mechanisms were identified: a) promotion of family carers' understanding about their family member's health condition, prognosis, and treatments available; b) fostering of shared decision-making between health care professionals (HCPs) and residents/family carers; and c) using and improving knowledge about residents' preferences. Conclusion: Family carers' understanding, shared decision-making, and knowledge of residents' preferences contribute to palliative-oriented care in NHs. Practice implications: Discussions about end-of-life should take place early in a resident's disease trajectory to allow time for family carers to understand the condition and participate in subsequent, mindful, shared decision-making. HCPs should conduct systematic and thorough discussions about end-of-life treatment options with all cognitively competent residents to promote informed advance directives.